Impact of the covid-19 pandemic on maternal and child nutrition and health ser-vices (MCH) - Indah Yun Diniaty Rosidi; Arisna Kadir (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: In Indonesia, East Java province, precisely in the Surabaya area, the number of mothers who are confirmed to be Covid-19 is 112 people. The Indonesian Pediat-rics Association (IDAI) conveyed data on child deaths due to Covid-19 in the country so far, overall, 70% of the cases of children died due to corona virus infection.Objectives: To describe the impact of the COVID-19 pandemic on nutrition and MCH servicesMethods: This research is a descriptive study with a quantitative approach and was carried out at the Makassar City Health Office in February - August 2021. In this re-search, secondary data was used with samples of nutrition and MCH service data, namely the coverage of K1 and K4 and the target of nutrition services for the period 2019-2020. . In this study, in-depth interviews were conducted online and in stages from the Health Office, Public Health Centre and preg-nant/breastfeeding/having children under five on changes in health services during the COVID-19 pandemic.Results: MCH services (K1 and K4 coverage) in 2019 K1 coverage was 96.8% and increased in 2020 by 97.14%, while K4 coverage in 2019 reached 92.58% and decreased to 92, 4% in 2020. Nutrition services that in 2019 the target for nutrition services is 84.52% and has decreased to reach 69.14% and will decrease further in 2021 (January-May) which is 67%.Conclusions: The description of the impact of the COVID-19 pandemic on nutrition and MCH services can be said that the number of visits to Nutrition and MCH services in the Makassar city area has generally decreased. This was mainly due to delays in IHC services. However, various efforts, such as maximizing home visits and monitoring the condition of mothers and babies via WhatsApp, can hamper the number of nutrition and MCH services.